Vertical and spatial evaluation of the groundwater chemistry in the Central Nile Delta Quaternary aquifer to assess the effects of human activities and seawater intrusion - Salem, Zenhom E.; ElNahrawy, Abdelaziz; Attiah, Abdullah M.; Edokpayi, Joshua N. (Frontiers in Environmental Science, 2022)
Contaminants can be found in the groundwater through natural processes such as seawater intrusion or as a results of human activities that can adversely affect the quantity, quality and distribution of the groundwater. For assessing the influence of the human activities and seawater intrusion on the groundwater chemistry in the Central Nile Delta region, groundwater was collected from 167 production wells having depths ranging from 15 to 120m. In addition, 8 soil-water samples were collected from depths of about 1m. The groundwater samples were divided based on well depths into 3 zones: shallow zone (< 40 m depth), intermediate zone (41 to 60 m depth) and deep zone (> 60 m depth). The TDS, EC, pH, K+, Na+, Mg2+, Ca2+, Cl-, HCO3-, SO42- were determined for all water samples. The groundwater samples having Cl between 100-200 mg/L and EC between 600-2000 µs/cm represent a mixing between freshwater and saltwater. Increasing of TDS and concentrations of all major ions toward the northern parts reflected the impact of the seawater intrusion. The groundwater had the Na/Cl ratio ranged from 0.46 to 2.75 indicating the influence of both seawater intrusion and anthropogenic activities on the groundwater chemistry. In addition, the high Ca/Mg, Ca/SO4 and Ca/HCO3 ratios (>1) indicated that the groundwater was intruded by seawater. The obtained water types, the ionic ratios and the saturation index results suggested that the anthropogenic activities, water-rock interaction, infiltration, mineral weathering and seawater intrusion are the main processes controlling the variation and evolution of the groundwater chemistry.